GERAKAN KOMUNITAS PEREMPUAN “SRIKANDI LINTAS IMAN” YOGYAKARTA DALAM TELAAH PENDIDIKAN ISLAM MULTIKULTURAL - Fatihaturrohmah Fatihaturrohmah; Ahmad Shofiyuddin Ichsan (PAI RAFAH, 2019)
This study aims to determine the activities of women's community "Srikandi Lintas Iman" Yogyakarta in muticultural Islamic education study, to know the implications of multicultural Islamic education in the women's community in managing religious diversity in Yogyakarta, and to find out the supporting factors in the movement process in women's community "Srikandi Lintas Iman”. This type of research is field research with a phenomenological approach. Data sources obtained through structured interviews, passive participant observation and documentation. Then, data analysis uses data analysis according to Cresswell. The results obtained that the women's community movement "Srikandi Lintas Iman" focused on several activities, namely cross-faith discussions, interfaith pilgrimages, and conflict resolution training. The implication is that their members are able to apply the values ​​of multicultural Islamic education, namely inclusive, tolerance, pluralism, justice, and peace. To understand the supporting factors of this women's community, they are solid in carrying out their vision and mission together, leader continues to be active in directing, members come from various backgrounds, and the family system between members is still maintained.